Replication of single viruses across the kingdoms, Fungi, Plantae, and Animalia - Telengech, Paul; Hyodo, Kiwamu; Ichikawa, Hiroaki; Kuwata, Ryusei; Kondo, Hideki; Suzuki, Nobuhiro (Proceedings of the National Academy of Sciences, 2024)
It is extremely rare that a single virus crosses host barriers across multiple kingdoms. Based on phylogenetic and paleovirological analyses, it has previously been hypothesized that single members of the family Partitiviridae could cross multiple kingdoms. Partitiviridae accommodates members characterized by their simple bisegmented double-stranded RNA genome; asymptomatic infections of host organisms; the absence of an extracellular route for entry in nature; and collectively broad host range. Herein, we show the replicability of single fungal partitiviruses in three kingdoms of host organisms: Fungi, Plantae, and Animalia. Betapartitiviruses of the phytopathogenic fungus Rosellinia necatrix could replicate in protoplasts of the carrot ( Daucus carota ), Nicotiana benthamiana and Nicotiana tabacum , in some cases reaching a level detectable by agarose gel electrophoresis. Moreover, betapartitiviruses showed more robust replication than the tested alphapartitiviruses. One of the fungal betapartitiviruses, RnPV18, could persistently and stably infect carrot plants regenerated from virion-transfected protoplasts. Both alpha- and betapartitiviruses, although with different host preference, could replicate in two insect cell lines derived from the fall armyworm Spodoptera frugiperda and the fruit fly Drosophila melanogaster . Our results indicate the replicability of single partitiviruses in members of three kingdoms and provide insights into virus adaptation, host jumping, and evolution.